Computing and the Crisis: The Significant Role of New Information Technologies in the Current Socio-economic Meltdown - David Hakken (tripleC: Communication, Capitalism & Critique)
There is good reason to be concerned about the long-term implications of the current crisis for the reproduction of contemporary social formations. Thus there is an urgent need to understand it character, especially its distinctive features. This article identifies profound ambiguities in valuing assets as new and key economic features of this crisis, ambiguities traceable to the dominant, “computationalist” computing used to develop new financial instruments. After some preliminaries, the article identifies four specific ways in which computerization of finance is generative of crisis. It then demonstrates how computationalist computing is linked to other efforts to extend commodification based on the ideology of so-called “intellectual property” (IP). Several other accounts for the crisis are considered and then demonstrated to have less explanatory value. After considering how some commons-oriented (e.g., Free/Libre and/or Opening Source Software development projects) forms of computing also undermine the IP project, the article concludes with a brief discussion of what research on Socially Robust and Enduring Computing might contribute to fostering alternative, non-crisis generative ways to compute.